Os modalizadores como estratégia semântico-argumentativa no gênero edital - Santos, Sandra Maria de Carvalho (2012)
The aim of this paper is to describe the functioning of modalizations as an argumentative-semantic strategy of the genre Public Notice, which purpose is to advertise or publicize the fact that must be known. It is a genre used by most of the public and private institutions in our country, but poorly studied, possibly because it is an official document of impersonal nature. Our corpus is composed by eight Public Notices. In the analyzes we describe the modalizations as an argumentative-semantic strategy present in the texts and the effects of meaning generated within the discourse. Our investigation,descriptive in nature, focusing on studies of modalization, proposed by several authors, as Castilho and Castilho (2002), Cervoni (1989), Lyons (1977), Koch (2000), Silva (2007), Nascimento (2009, 2010), Silva e Nascimento (2012), among others, and supports itself in the concept of argumentation by Ducrot and his collaborators (1988 and 1994). The theoretical approach allowed us to understand how these modalizations work strategically in that genre.It was observed along the stretches analyzed,that the deontic modals and delimiters were the most used, demonstrating the concern of the speakers to leave marks on the statements, in order to maintain constant dialogue with their interlocutors, reporting, therefore, a strong commitment on the part of the responsibles for the speeches. These linguistic-discursive elements have functioned not only as indices of subjectivity in the texts, indicating a positioning of the speaker forward to what was said, but also as indicators of intersubjectivity, in other words, they are used by the speaker to interact with his interlocutor, indicating how this one should act. The presence of modal constitutes a characteristic of the Public Notice due to its instructional nature genre given the instructional nature of the Public Notice, that often more than make public a certain fact, as a public selective exam, a concurrence etc., it guides the interested parties (intelocutors) how to act and what procedures to take upon what is being published.